Union/Nonunion Wage Gaps in the Public Sector - Lewis, H. Gregg (Journal of Labor Economics, 1990)
There is much variation in the union/nonunion wage gap across groups of workers within each of the two sectors, public and private. Furthermore, the variation in the public sector does not parallel in all of its detail that in the private sector. Thus, though the public-sector gaps typically are somewhat below their private-sector counterparts, there are important exceptions to this difference, especially among employees of local governments: public school teachers, clerical workers, refuse collectors, local transit bus drivers, licensed practical nurses, hospital technicians, nonprofessional hospital workers, and undoubtedly some others.